Cartera vencida del Gobierno Autónomo Descentralizado (GAD) Municipal del Cantón Vinces en la provincia de Los Ríos en el periodo 2021 – 2022. - Bustamante Zambrano, Yandry Yahir (2024)
The following case study addresses issues related to the financial difficulties faced by the municipal Decentralized Autonomous Government (GAD) of the Vinces canton during the period 2021-2022, especially related to the management of the overdue portfolio. The lack of monitoring, surveillance and debt collection stands out as the main causes of this problem, which has led to a significant deterioration in the financial situation of the institution. This deterioration not only affects the GAD's ability to fulfill its municipal responsibilities, but also negatively affects citizens' confidence in its ability to properly manage financial resources. The accumulation of unpaid debts has affected the GAD's ability to finance essential projects and programs, which translates into an institutional deterioration and the quality of life of the local population. It is therefore crucial to comprehensively address the causes of these deficiencies to implement effective solutions and promote more robust and sustainable financial management, thus ensuring the well-being of the local community and the long-term viability of the Vinces municipal GAD.